Features of Formation and Development of the Youth Segment of the Regional Labour Market - Kabachenko, G. (Економічний вісник Донбасу, 2015)
The article examines the features of formation and development of the youth segment of the regional labor market, carried out assessment of youth employment in the Donetsk region, identified the problems of youth employment in the conditions of socio-economic imbalances and propose measures to address youth employment issues. The study proved that there are many challenges for youth employment in modern conditions of economic development, which requires the development of effective measures to address them. It was found that for the expansion of youth employment opportunities advisable to carry out pioneer work with young students of secondary schools, their parents and teachers, to strengthen the process of creating career development portfolio, to ensure the formation of self-presentation skills among young people by bringing them to training on techniques of job search that will enhance the level of youth employment, improving the conditions of functioning of vocational guidance systems, increased economic activity and the competitiveness of young people on the labor market, reduce the level and duration of unemployment. У статті досліджуються особливості становлення та розвитку молодіжного сегменту на регіональному ринку праці, здійснено оцінку стану молодіжної зайнятості у Донецькому регіоні, визначено проблеми молоді при працевлаштуванні в умовах соціально-економічного дисбалансу та запропоновано заходи щодо вирішення проблеми зайнятості молоді. В ході дослідження обґрунтовано, що в сучасних умовах розвитку економіки існує безліч проблем із забезпечення зайнятості молоді, які потребують розробки дієвих заходів щодо їх вирішення. Встановлено, що для розширення можливостей працевлаштування молоді доцільно проводити випереджальну роботу з учнівською молоддю загальноосвітніх шкіл, їх батьками та педагогами, активізувати процес створення портфоліо кар’єрного просування, забезпечити формування навичок самопрезентації у молоді шляхом залучення їх до тренінгів з техніки пошуку роботи, сприятиме підвищенню рівня зайнятості молоді, покращенню умов функціонування системи профорієнтації, підвищенню економічної активності та конкурентоспроможності молоді на ринку праці, зниженню рівня та тривалості безробіття. В статье исследуются особенности становления и развития молодежного сегмента на региональном рынке труда, осуществлена оценка состояния молодежной занятости в Донецком регионе, определены проблемы молодежи при трудоустройстве в условиях социально-экономического дисбаланса и предложены мероприятия по решению проблемы занятости молодежи. В ходе исследования обосновано, что в современных условиях развития экономики существует множество проблем по обеспечению занятости молодежи, которые требуют разработки действенных мероприятий по их решению. Установлено, что для расширения возможностей трудоустройства молодежи целесообразно проводить опережающую работу с учащейся молодежью общеобразовательных школ, их родителями и педагогами, активизировать процесс создания портфолио карьерного продвижения, обеспечить формирование навыков самопрезентации у молодежи путем привлечения их к тренингам по технике поиска работы, что будет способствовать повышению уровня занятости молодежи, улучшению условий функционирования системы профориентации, повышению экономической активности и конкурентоспособности молодежи на рынке труда, снижению уровня и продолжительности безработицы.